2013
DOI: 10.1111/aji.12103
|View full text |Cite
|
Sign up to set email alerts
|

The Multiple Faces of the Decidual Natural Killer Cell

Abstract: The decidual NK (dNK) cell is called on to support placental growth by providing an array of growth factors that directly transform the spiral artery and direct trophoblast invasion. Successful transformation is dependent upon adequate stimulation paradoxically stimulating the cell for placental support rather than cytotoxicity. With the identification of its supportive role, the presence of an intact cytotoxic mechanism has been confusing. Investigators have found that the cell remains fully capable of cytoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…pNK cells are mainly responsible for fighting pathogen infections via secretion of perforin and granzymes, but dNK cells participate in fetomaternal immune tolerance, trophoblast invasion and vascular remodeling through secretion of various types of cytokines. 15,36 The environment at the maternal-fetal interface is assumed to modify recruited pNK cells, instructing them to be dNK-like cells in phenotype and function. 28,37 Here, we found that the coculture of pNK cells with trophoblasts significantly increased Th2-type cytokine production and decreased Th1-type cytokine and perforin expression by pNK cells.…”
Section: Cd16mentioning
confidence: 99%
“…pNK cells are mainly responsible for fighting pathogen infections via secretion of perforin and granzymes, but dNK cells participate in fetomaternal immune tolerance, trophoblast invasion and vascular remodeling through secretion of various types of cytokines. 15,36 The environment at the maternal-fetal interface is assumed to modify recruited pNK cells, instructing them to be dNK-like cells in phenotype and function. 28,37 Here, we found that the coculture of pNK cells with trophoblasts significantly increased Th2-type cytokine production and decreased Th1-type cytokine and perforin expression by pNK cells.…”
Section: Cd16mentioning
confidence: 99%
“…Recent evidence has suggested that Tregs can directly control NK cell activity 19 . Since uterine NK cells are phenotypically distinct from those found in the periphery, it is not clear if those findings are applicable 20 . It is clear that uterine NK cells are necessary to support pregnancy, but retain the potential to cause pathology 20 .…”
Section: Discussionmentioning
confidence: 99%
“…19 As uterine NK cells are phenotypically distinct from those found in the periphery, it is not clear if those findings are applicable. 20 It is clear that uterine NK cells are necessary to support pregnancy, but retain the potential to cause pathology. 20 Perhaps local Tregs modulate NK cell activity to favor a permissive environment for pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…1 As the predominant innate immune cells during gestation, natural killer (NK) cells have been proven to mediate the establishment of maternal-fetal immune tolerance and to initiate appropriate defenses against infections. 2 Tim-3, a member of the T-cell immunoglobulin and mucin domain proteins, has emerged as a key molecule in both innate and adaptive responses and represents a promising novel therapeutic target. 3,4 The expression of Tim-3 has been shown to associate with the maturation or activation of NK cells, and the surrounding immune microenvironment of NK cells also exerts some influence on Tim-3 expression.…”
mentioning
confidence: 99%